ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE BERDASARKAN ASEAN CORPORATE GOVERNANCE SCORECARD PADA PT BPD BALI: ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE BERDASARKAN ASEAN CORPORATE GOVERNANCE SCORECARD PADA PT BPD BALI - Novia Sari; Putu Ngurah Suyatna Yasa; A.A. Gede Krisna Murti (Jurnal Riset Akuntansi Warmadewa, 2024)
This research aims to be able to evaluate the extent to which the implementation of various principles in the form of Good Corporate Governance at PT BPD Bali uses the ASEAN Corporate Governance Scorecard assessment framework which is an evaluation tool. This research focuses on three aspects of assessment, namely, first in the form of the role of stakeholders, second in the form of disclosure, and third in the form of transparency and the responsibility of two parties, namely the board of directors and also the board of commissioners. The research method used is a qualitative approach in the form of document content analysis guided by the ACGS assessment framework, using the steps of the Miles and Huberman analysis model. This research uses secondary data in the form of documents "2023 Annual Report", "2023 Governance Implementation Report", "2023 Sustainability Report" and other information which is relevant to the scope of this research which was obtained through the PT BPD Bali website. . The research results show that PT BPD Bali has implemented most of the components from these three aspects well, but there are still several components that need to be improved because these components have not been implemented by PT BPD Bali, so the value obtained has not reached the maximum value. PT BPD Bali received a final score of 62.7 out of the maximum possible score of 80. In detail, it got a score of 12.69 out of a maximum score of 15 for the Stakeholder Role Aspect, a score of 21.09 out of a maximum score of 25 for the Disclosure and Transparency Aspect, and received a score of 28.92 out of a maximum score of 40 for the Responsibility Aspect from two parties, namely the first in the form of the Directors and the second in the form of the Board of Commissioners.